2009
DOI: 10.1016/s0924-9338(09)71173-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Self - Care Program on the Self- Esteem of Multiple Sclerosis Patients

Abstract: Aims:According to decreased self- esteem in multiple sclerosis (MS) patients, it is necessary to utilize appropriate methods in order to improve self- esteem in MS patients. So this study was conducted on patients with MS supported by the Iranian MS society for determining the effect of self - care program on their self- esteem.Method:In this semi - experimental study 34 patients with MS who were not in the acute phase of disease were selected. The data were collected via personal questionnaires, problem list,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The effect of debilitating chronic diseases such as MS and their attendant problems, including the impact of disability on quality of life in all dimensions is obvious [22]. Increasing the consumption of folic acid and vitamin B12 improved physical and mental dimensions of quality of life which is in line with the findings of our study [23].…”
Section: Discussionsupporting
confidence: 86%
“…The effect of debilitating chronic diseases such as MS and their attendant problems, including the impact of disability on quality of life in all dimensions is obvious [22]. Increasing the consumption of folic acid and vitamin B12 improved physical and mental dimensions of quality of life which is in line with the findings of our study [23].…”
Section: Discussionsupporting
confidence: 86%
“…Therefore, its total score ranges from 35 to 140, with higher scores illustrating higher self-esteem. In the study by Madani et al .,[ 39 ] the reliability of the CSEI was confirmed using the correlation coefficient (r = 93%). The Cronbach's alpha coefficient obtained by the researcher was 0.97.…”
Section: Methodsmentioning
confidence: 93%
“…In third field, Well-Being Education in four sections accepted, A: Nutrition; B: Health Promotion; C: Life Style Improvement and D: Patient Activity. Majority of surveys reported that had information about mobility were very important for self management ( 46 , 47 , 56 , 57 , 58 , 59 , 60 ) and education could improved life style ( 61 , 62 , 63 , 64 ) and proposed that the manner of mobility, programming for exercise, jogging and rest educated to patient. These finding was the same as us results, but on the other hand related to other people suffering the same disease resulted to better self management ( 65 , 66 ).…”
Section: Discussionmentioning
confidence: 99%